Enhancing Flood Disaster Knowledge and Preparedness among Health Vocational Students: Evidence from a School-Based Education Program - Rina Wijayanti; Dina Raidanti; Wahidin Wahidin; Septia Dwi Lestari (Utan Kayu Publishing, 2026)
Flood disasters are frequent hydrometeorological hazards in Indonesia and may disrupt school safety, learning continuity, and students’ health. This study examined whether flood disaster preparedness education was followed by improvements in students’ knowledge and preparedness and analyzed the association between both variables at Letris Indonesia 2 Health Vocational School, Tangerang. A quantitative pre-experimental study with a one-group pretest–posttest design was conducted among 30 students who completed all stages of the study. The intervention consisted of three 60-minute educational sessions covering flood causes, early warning signs, evacuation procedures, emergency kits, emergency communication, first aid, post-flood sanitation, and disease prevention. Data were collected using validated and reliable questionnaires. Because score differences were not normally distributed, pretest–posttest changes were analyzed using the Wilcoxon signed-rank test, while the association between knowledge and preparedness was examined using Spearman’s rho. Students’ knowledge increased significantly from a median of 60.00 to 82.00 (Z = -4.72, p < .001, r = 0.86). Preparedness also increased from a median of 52.00 to 78.00 (Z = -4.78, p < .001, r = 0.87). Knowledge was strongly associated with preparedness (rho = 0.871, p < .001). Flood disaster preparedness education was associated with short-term improvements in students’ knowledge and self-reported preparedness.